Penggunaan Pewarna Alami dan Pengisi Jamu Instan Bagi UKM Obat Tradisional - Syaiful Choiri; Estu Retnaningtyas Nugraheni; Rita Rakhmawati; Ahmad Ainurofiq; Saptono Hadi; Dinar Sari Cahyaningrum Wahyuni (Universitas Muhammadiyah Yogyakarta, 2023)
The demand for traditional medicine increased during the pandemic, including instant herbal medicine for children. Children who consume herbal medicine are more interested in colorful products according to the advertised taste, while adult consumers are more interested in herbal compositions that are slightly sweeter (less sugar). This service aims to provide alternative natural dyes and non-sugar fillers for instant herbal products. Accordingly, the service was carried out in two stages. The service program was carried out using the tutorial method and focus group discussions (FGD). Tutorials were carried out online with natural materials as a source of alternative natural dyes and innovations in the use of non-sugar fillers. Group discussions focused on innovations in using non-sugar fillers with low production costs. The results showed that Rosella flowers (Hibiscus sabdariffa L.) are recommended as natural dyes for instant herbal medicine for children for red, yellow, and purple colors, while Suji leaves (Dracaena Angustifolia) for green colors. Additionally, Maltodextrin Fluidized Bed Dryer (FBD) ) is recommended as a non-sugar filler.